Diagnosing iMN (Idiopathic Membranous Nephropathy); Research Opportunities via ISN: Crossing The Geographical Boundaries - Riaz, Muhammad Mohsin; Sabir, Omer (Pakistan Journal of Kidney Diseases, 2021)
Membranous nephropathy (MN) still remains one of the common causes of adult glomerulonephritis and leading cause of CKD (chronic kidney disease) and ESRD (end stage renal disease) in adult population. Differentiating between idiopathic (iMN) and secondary membranous nephropathy (sMN) is of key importance. The treatment and prognosis for both types vary. Phospholipase A2 receptor (PLA2R) has been shown as major auto-antigen in iMN. Its prevalence ranges from 70% – 80% in cases of iMN as described by international studies. The prevalence of PLAR in iMN from our region is not known. This study was conducted to look into prevalence of PLA2R in iMN patients from our population. While carrying out study we found some other important factors that affect the diagnostic histopathology, collectively termed as pre-analytical factors. We also found that there are no standardized protocols for performing the immunohistochemistry (IHC) studies and only set of guidelines are available. The important component of diagnostic histopathology i.e. electron microscopy is also missing in the process of making tissue diagnosis.